2017
DOI: 10.1186/s12916-016-0759-3
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of placental mTOR signaling provides a link between placental malaria and reduced birthweight

Abstract: BackgroundPlacental Plasmodium falciparum malaria can trigger intervillositis, a local inflammatory response more strongly associated with low birthweight than placental malaria infection alone. Fetal growth (and therefore birthweight) is dependent on placental amino acid transport, which is impaired in placental malaria-associated intervillositis. Here, we tested the hypothesis that mechanistic target of rapamycin (mTOR) signaling, a pathway known to regulate amino acid transport, is inhibited in placental ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
152
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(163 citation statements)
references
References 51 publications
8
152
2
1
Order By: Relevance
“…At moderate levels, HNE promotes organelle and protein damage leading to induction of autophagy (45). Inhibition of mTOR signaling has recently been shown to provide a link between human PM and low birth weight (46), but has not been explored in the context of malaria-induced oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…At moderate levels, HNE promotes organelle and protein damage leading to induction of autophagy (45). Inhibition of mTOR signaling has recently been shown to provide a link between human PM and low birth weight (46), but has not been explored in the context of malaria-induced oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Pregnant women are susceptible to severe Plasmodium falciparum infection because of alteration of acquired antimalarial immunity due to parasites (VAR2CSA) that sequester in the placenta [7,8]. The Plasmodium falciparum impairs the capacity of the placenta to transport amino acids from maternal blood to the foetus, and therefore contributing to low birth weights (LBW) [9]. Other consequences of malaria infection in pregnancy are increased risk of severe anaemia, cerebral malaria, pre-term delivery, intrauterine growth retardation, maternal death and increased risk to unborn baby from miscarriage [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to our findings, a previous study by Dimasuay et al had demonstrated that the activity of both mTOR complexes is decreased in placental malaria with intervillositis, as evidenced by the reduced content of mTORC1 downstream products phosphoS6 and phospho4EBP1 and mTORC2 downstream product phosphoAKT S473. In addition, they also showed that mTOR inhibition was associated to high levels of the cytokines IL-1␤, IL-6, IL-8, TNF and IL-10 which are secreted by monocytes exposed to infected erythrocytes (40). A possible reason to explain the discrepancy in mTORC1 and 2 activities between both studies relies in the fact that, in contrast to Dimasuay et al (40), our experiments were performed in past-infected placentas where no parasites or intervillositis were found (supplemental Table S2).…”
Section: Molecular and Cellular Proteomics 182 195mentioning
confidence: 99%
“…It is well known that fetal growth is directly related to maternal nutrient availability and ability to transport these nutrients from maternal circulation to the fetus (35,36). The rupture of amino acid transport in malaria-infected placentas with intervillositis was recently correlated with reduced birth weight (40). Moreover, protein folding and protein catabolic process (ubiquitin-dependent protein catabolism, proteasomal protein catabolism) are also important biological processes related to cell metabolism, survival, and adaptation to cell stress (41,42).…”
Section: Molecular and Cellular Proteomics 182 193mentioning
confidence: 99%